Confiscated assets into public heritage - Marina Tornatora; Ottavio Amaro (Techne)
The research, as result of an agreement with the Calabria Region, aims to consolidate a corpus of investigations developed over the years by the Landscape_inProgress Laboratory, which examines the forms produced by criminal actions in urban transformation processes by studying property confiscated from the mafias. The investigation proposes a different approach to provide the opportunity to develop strategies for urban and architectural regeneration of cities, bringing out a “third public heritage” to be “re-injected” into urban and territorial policies. A matter to be “rewritten” for new life cycles. The “Impronte a Sud_WelfareLab” project, implemented in Reggio Calabria for Consorzio Macramè on a confiscated asset, is a best practice that combines management, functional, and urban processes with an aesthetic and architectural metamorphosis.